Age-Related Changes on CD40 Promotor Methylation and Immune Gene Expressions in Thymus of Chicken - Li, Yulong; Lei, Xinyu; Lu, Hong; Guo, Wei; Wu, Shengru; Yin, Zhenchen; Sun, Qingzhu; Yang, Xiaojun (Frontiers in Immunology, 2018)
120 one-day-old breeder cocks, included 15 cages of 8 birds each, were fed to learn the aging's effect on chicken’s thymus immunity. At 2 (2-W) and 40 (40-W) weeks of age, one chicken each cage was randomly chosen and slaughtered to get the thymus sample. The results showed that thymus weight and morphology of 40-W group were far different from that of 2-W group, and exhibited a property of degeneration. Considering this phenotype variances, we analyzed the thymus’ transcriptome to investigate the molecular mechanism that had been implicated in this phenotype diversity with age. Pearson correlation coefficients and principal component analysis indicated that two major populations corresponding to 40-W and 2-W group were identified, and 1949 differentially expressed genes (DEGs, 1722 up-regulated and 127 down-regulated) were obtained. Results of GO and KEGG pathway enrichment found that 4 significantly enriched KEGG pathways (Cytokine-cytokine receptor interaction, Intestinal immune network for IgA production, Toll-like receptor signaling pathway, AGE-RAGE signaling pathway in diabetic complications) related to immune-regulation were screened between 40-W and 2-W group. These results confirmed that thymus immunity of chickens had a strong age-related correlation. DEGs related to these 4 enriched KEGG pathways were suppressed in the thymus of 2-W group, this indicated that thymus immunity of 2-weeks-age chick was down-regulated. CD40 is involved in 3 of the 4 significantly enriched pathways, and it is critical for thymus immune-regulation. CD40 promoter methylation level of 2-W group was higher than that of 40-W group, it is consistent with the transcriptional differences of the gene. Our study concluded that thymus immunity of chicken was varied with age. Compared to the 40-W group, thymus immunity of 2-W group was down-regulated, and in a status of hypo-activation on the whole, and these effects might be related to CD40 suppression induced by promoter hyper-methylation of the gene.